2003
DOI: 10.1096/fj.02-0626fje
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and functional analyses of the contractile apparatus in lymphatic muscle

Abstract: Lymphatics are necessary for the generation and regulation of lymph flow. Lymphatics use phasic contractions and extrinsic compressions to generate flow; tonic contractions alter resistance. Lymphatic muscle exhibits important differences from typical vascular smooth muscle. In this study, the thoracic duct exhibited significant functional differences from mesenteric lymphatics. To understand the molecular basis for these differences, we examined the profiles of contractile proteins and their messages in mesen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
187
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(196 citation statements)
references
References 38 publications
(49 reference statements)
9
187
0
Order By: Relevance
“…Our previous studies demonstrated regional heterogeneity in the contractile behavior of lymphatic vessels. 10,13,25 Our current studies provided the first evidence of regionally different influence of aging on different lymphatic networks. To illustrate such conclusions, we compared isolated MLV data with published data 4 obtained from experiments utilizing isolated rat TD segments from similar groups of adult (9-mo old) and aged (24-mo old) F-344 rats and treated with similar experimental conditions.…”
mentioning
confidence: 55%
“…Our previous studies demonstrated regional heterogeneity in the contractile behavior of lymphatic vessels. 10,13,25 Our current studies provided the first evidence of regionally different influence of aging on different lymphatic networks. To illustrate such conclusions, we compared isolated MLV data with published data 4 obtained from experiments utilizing isolated rat TD segments from similar groups of adult (9-mo old) and aged (24-mo old) F-344 rats and treated with similar experimental conditions.…”
mentioning
confidence: 55%
“…In this respect, the behavior of lymphatics and small veins resembles that of phasic visceral smooth muscle (29). Our previous molecular analyses of the contractile apparatus demonstrated that mesenteric lymphatic muscle appears to have more organized contractile elements and different expression levels of contractile proteins, especially myosin heavy chains and actin, than do mesenteric arteries (36). This distinctly different composition of lymphatic contractile machinery in mesenteric lymphatics as well as the composition of the extracellular connective tissue matrix (14,23,38) might also contribute to the differences in the active length-tension relationship between arterial, venous, and lymphatic vessels.…”
Section: H1948 Length-tension Relationships Of Arteries Veins Lymphmentioning
confidence: 95%
“…Furthermore, comparisons between arterial, venous, and lymphatic vessels in the same vasculature do not exist. A recent study (36) demonstrated that muscle cells in rat mesenteric lymphatics have unique contractile machinery composed of both smooth and striated muscle components. Rat mesenteric lymphatic vessels also exhibit contractile characteristics different from lymphatics in other regions of that species (18,19).…”
mentioning
confidence: 99%
“…We (37) have previously shown that lymphatic muscle is structurally composed of both smooth and striated muscle contractile elements and functionally shares similarities with both cardiac muscle and VSM. This correlates well with the unique functional aspects of both tonic and phasic lymphatic contractions.…”
Section: M) Immunohistochemical and Western Blot Analyses Of Pmlc20mentioning
confidence: 98%